Preventing Workplace Violence in Healthcare: Strategies to Reduce Medical Disputes and Enhance Patient Safety-An Updated Review for Healthcare Security Workers - Awaji, Abeer Ali Ali; Fahad Abdullah Mohammad Alhanaya; Arwa Zaidan Alzaidan; Sumayyah Abdu Yahya Hadadi; Ismail Mohammed Abdullah Sahli; Hassan Yahya Ahmed Najmi; Amjad Abdulaziz Mohammed Aljallal; Ghalib Mohammed Abdu Arar; Abdullah Mohammed Ahmed Asiri (Saudi Journal of Medicine and Public Health, 2025)
Background: Workplace violence against healthcare professionals (HCPs) undermines staff safety, erodes trust, and jeopardizes patient outcomes. In many settings, rising legal consciousness among patients and persistent quality deficits intersect with structural, financial, and educational weaknesses to intensify medical disputes and the risk of aggression. Aim: To synthesize an updated, practice-oriented framework for healthcare security workers and institutional leaders to prevent workplace violence, reduce medical disputes, and enhance patient safety through system, organizational, and frontline interventions. Methods: Narrative integration of recent analyses on root causes of violence and disputes, encompassing governance and accountability structures, purchasing and payment reforms, regulatory oversight, medical education quality assurance, workforce distribution, institutional safety systems, communication practices, and complaint and mediation pathways. Emphasis was placed on interactions between patient rights awareness, service quality, and trust. Results: Two proximate drivers—heightened awareness of patient rights and uneven service quality—amplify conflict when grievance mechanisms are weak. Structural factors include distorted competition dominated by public hospitals, fragmented governance with diffuse accountability, payer fragmentation with feeforservice and basic capitation that do not reward outcomes, and medical education expansion outpacing capacity. Media effects are indirect, primarily amplifying postincident norms. Financial toxicity and low institutional trust mediate escalation. Effective strategies include empowering hospital directors with authority tied to multidimensional performance accountability; integrating insurance purchasing and adopting blended payments (global budgets plus DRGs) with quality guardrails and public reporting; tightening medical school accreditation and rightsizing enrollment; deploying comprehensive safety and incidentlearning systems; strengthening patient communication, transparency, and apology practices; and institutionalizing rapid, fair complaint resolution and mediation, supported by targeted deescalation training for security and clinical teams. Conclusion: A layered, qualitycentered prevention model—aligning governance, purchasing, education, safety culture, and grievance systems—can reduce violence, resolve disputes earlier, and measurably improve patient and workforce safety.